Effects of feeding fermented rice bran on the growth performance of broiler - Sahdan, N. I. J.; Abdullah, Norhani; Samsudin, A. H.; A. J., Azilah (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Rhizopus sp. was used to improve the nutritive value of rice bran (RB) by solid state fermentation (SSF). The optimized conditions for SSF were moisture 45ml/50g substrate, pH 7.0, temperature 30°C and ammonium sulphate 1% for 36h incubation. The crude protein, soluble protein and reducing sugar increased, while the crude fibre decreased by about 24%. Three diets were formulated for the growth performance study in broiler chicken. Diet A - control (soybean meal-corn based diet), Diet B contained 20% untreated RB and Diet C contained 20% fermented RB. From day 1 to day 21, 180 broiler Cobb were fed commercial diet and at day 22, the broilers were randomly assigned into 3 groups with 5 replicates. The results showed that the final body weights of broilers at day 35 were not significantly different among diets. The weights were 2.52±0.09, 2.44±0.06 and 2.50± 0.14 kg/bird for broilers fed control diet, Diet B and Diet C, repectively. Broilers fed RB showed lower feed intake compared to the broilers in the control group. The FCR values of broilers (1.64±0.02, 1.66±0.04, 1.56±0.13, respectively) were not significantly different among dietary treatments, although broilers fed Diet C showed slightly lower FCR. Fungal fermentation enhanced the nutritive value of RB and broilers fed diet containing 20% of fermented RB during the grower-finisher period showed slight improvement in feed efficiency when compared to broilers fed untreated RB.